How the perfectionistic climate of a sports team predicts the athletic performance of elite athletes: a case study of the CUBAL women’s basketball team - Meng, Meng; Su, Rong-Hai; Kogiso, Kohei; Zheng, Rong-Rong; Chen, Lin; Wei, Wei; Li, Wei; Hsu, Mao-Chou (Frontiers in Psychology, 2024)
Objective: In competitive sports, understanding how the perfectionistic climate within teams influences the performance of elite female athletes can provide valuable insights for enhancing coaching practice and athletic achievement. Based on the cognitive appraisal theory of stress, this study constructs a dual-path model using stressors and coping strategies as mediators, referred to as the Perfectionistic Climate on Athletic Performance model (PCPM). The study explores the predictive role of the perfectionistic climate within sports teams on the athletic performance of elite female basketball players. Methods: The empirical study the relationships among the variables in the model using a sample of 125 core players from the top-level women’s basketball teams in the 24th CUBAL24 tournament in 2022. A Structural Equation Modeling (SEM) analysis was conducted using AMOS 20.0, primarily employing the bias-corrected Bootstrap method to test the dual-path model. Results: The findings reveal double-edged paths towards a perfectionistic climate on athletic performance. In the positive pathway, a perfectionistic climate can positively predict athletic performance through challenge-related sources of stress and positive coping strategies. In the negative pathway, a perfectionistic climate can negatively predict athletic performance through threat-related sources of stress and negative coping strategies. Conclusion: Coaches need to pay attention to athletes’ cognitive evaluations of the perfectionistic climate as a source of pressure. By setting challenging goals, coaches can guide athletes to view the perfectionistic climate of the sports team as a source of challenging pressure, thus unleashing their potential. Coaches should actively guide athletes in coping with the pressure brought about by the perfectionistic climate, enhancing their ability to handle stress. This will enable athletes to better adapt to the team’s perfectionistic climate and further improve individual and team athletic performance.